White Adipose Tissue Surface Expression of LDLR and CD36 is Associated with Risk Factors for Type 2 Diabetes in Adults with Obesity. Issue 12 (11th October 2020) - Cyr, Yannick; Bissonnette, Simon; Lamantia, Valérie; Wassef, Hanny; Loizon, Emmanuelle; Ngo Sock, Emilienne T.; Vidal, Hubert; Mayer, Gaétan; Chrétien, Michel; Faraj, May
Abstract : Objective: Human conditions with upregulated receptor uptake of low‐density lipoproteins (LDL) are associated with diabetes risk, the reasons for which remain unexplored. LDL induce metabolic dysfunction in murine adipocytes. Thus, it was hypothesized that white adipose tissue (WAT) surface expression of LDL receptor (LDLR) and/or CD36 is associated with WAT and systemic metabolic dysfunction. Whether WAT LDLR and CD36 expression is predicted by plasma lipoprotein‐related parameters was also explored. Methods: This was a cross‐sectional analysis of 31 nondiabetic adults (BMI > 25 kg/m 2 ) assessed for WAT surface expression of LDLR and CD36 (immunohistochemistry), WAT function, WAT and systemic inflammation, postprandial fat metabolism, and insulin resistance (IR; hyperinsulinemic‐euglycemic clamp). Results: Fasting WAT surface expression of LDLR and CD36 was negatively associated with WAT function ( 3 H‐triglyceride storage, r  = −0.45 and −0.66, respectively) and positively associated with plasma IL‐1 receptor antagonist ( r  = 0.64 and 0.43, respectively). Their expression was suppressed 4 hours postprandially, and reduced LDLR was further associated with IR (M/Iclamp, r  = 0.61 women, r  = 0.80 men). Plasma apolipoprotein B (apoB)‐to‐PCSK9 ratio predicted WAT surface expression of LDLR and CD36, WAT dysfunction, WAT NLRP3 inflammasome priming and disrupted cholesterol‐sensing genes, and systemic IR independent of sex and body composition. Conclusions: Higher fasting and lower postprandial WAT surface expression of LDLR and CD36 is associated with WAT dysfunction, systemic inflammation, and IR in adults with overweight/obesity, anomalies that are predicted by higher plasma apoB‐to‐PCSK9 ratio.